Moral and Social Education in the Hadith of the Prophet: Analysis of Its Values and Relevance to Modern Islamic Education - Maslani Maslani; Rifdaa Aulia; Siti Fatmawati; Siti Sutiawati; Rijalul Haq; Khairuddin Manurung (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to examine the concept of moral and social education in the hadiths of the Prophet Muhammad SAW and its relevance to modern Islamic education. What distinguishes this study from previous studies is the use of implicit hadiths in explaining moral and social educational values that have never been discussed before. Using a descriptive qualitative approach, accompanied by three main methods, namely literature study, documentation, and contextual analysis, data were collected directly from hadith texts that specifically discuss moral and social education, as well as various supporting literature, including books on hadith interpretation, scientific journal articles, previous studies, and Islamic education literature relevant to this topic. The results of the study show that moral and social education are two integral dimensions that cannot be separated. The Prophet's hadiths emphasise the value of piety, the habit of doing good deeds, the virtue of morals as an indicator of the perfection of faith, and the importance of ukhuwah, solidarity, and mutual assistance in social life. These values are highly relevant to the needs of modern Islamic education, which demands a balance between spiritual, moral, and social aspects amid the challenges of character degradation and individualism. This study emphasises the importance of internalising the values of hadith in the curriculum through habit formation, role modelling, and character building to shape a generation with noble character. Further research is recommended to develop an operational curriculum model based on the integration of moral and social values and to conduct comparative studies to assess the effectiveness of the methods of internalising hadith and riyadah al-nafs in various educational contexts